Hubungan Usia, Pendidikan dan Pengetahuan dengan Kepatuhan Penerapan Protokol Kesehatan COVID-19 Masyarakat di Puskesmas Menteng - Talent, Greis Febiany; Arifin, Syamsul; Ratnasari, Arini (Barigas: Jurnal Riset Mahasiswa, 2023)
Coronavirus Disease 2019 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV - 2). COVID-19 was first reported in the city of Wuhan, and in March 2020 the WHO officially designated COVID-19 as a pandemic. The government's efforts in breaking the chain of transmission of COVID-19 are by urging the public to implement health protocols. The health protocol in question is to apply 3M, namely using a mask, cleaning hands regularly using soap or antiseptic liquid, and maintaining a minimum distance of 1 meter. The purpose of this study was to analyze whether there is a relationship between age, education, and knowledge with compliance with the implementation of community COVID-19 health protocols at Menteng Health Centers. This study is an observational analytic study with a cross sectional approach. Sampling using Lemeshow formula, with the number of respondents as many as 100 respondents. The Data used in this study is primary data, taken using a questionnaire instrument and data analysis using Chi Square test. Showed that there was a relationship between age p = 0.001 (p < 0.05), education p = 0.001 (p < 0.05) and knowledge p = 0.001 (p < 0.05) and compliance with the implementation of COVID-19 health protocols at Menteng Health Centers. There is a relationship between age, education and knowledge with compliance with the implementation of community COVID-19 health protocols at Menteng Health Centers.